3D digitalizacija in vizualizacija situle z Vač - Vidmar, Gregor (Knjižnica, 2012)
The project of 3D digitisation and visualisation of the Vače situla was implemented at the beginning of 2011 in cooperation with the National Museum of Slovenia where the situla is kept and the company MFC.2 which, among other services, develops and implements 3D digitisation and visualisation projects. The purpose of the project was to digitise and visualise a famous and precious piece of cultural heritage and to 1. show what modern 3D shape and texture scanning technologies allow us to do, 2. show how to ensure safety and reach high quality in digitising cultural heritage objects, 3. measure the added value of the 3D visualisation of cultural heritage as a powerful tool for preservation, conservation, research, education, knowledge sharing and promotion of cultural heritage objects. Furthermore, the aims of the project were: 1. 3D capture of the shape and texture of the situla using the 3D scanning method, 2. 3D image of the situla and its details with expert descriptions, 3. 3D stereoscopis projection of the situla viewed with 3D glasses and with the possibility of controlling it remotely, 4. 3D animation giving professional interpretation of certain facts about the situla, 5. public presentation of the project results on Slovenian cultural holiday, 8th February 2011, at the National Museum of Slovenia. The 3D capture of the shape and texture of the situla was carried out using the white light 3D scanning method followed by 3D flesh animation to show the object and its details. A touch screen was used to provide user access to the content. Reality based model enabled vertical rotation of the situla as well as the interactive display of individual engravings. By clicking a situla detail a photo with an extensive professional explanation of the scene was displayed in a new browser window. For attractive public presentation of the exhibition a 3D stereoscopic animation of the situla rotating and seemingly floating in the atrium of the National Museum of Slovenia was displayed. Visitors had the possibility to view the animation with 3D glasses and to navigate the floating situla remotely. Furthermore, a 3D animation of the situla history was created and entitled the Story of the Vače situla. Based on expert interpretation it presented the origins of the situla, the period in which it was produced, the geographic area where its production was spread, usability of situlas and its discovery in Vače at the end of 19the century. The animation includes text, sound and picture presentation of the situla and is enriched by animation of one of small figures depicting everyday life and tasks among the people. The aims of the project were presented to public on Slovenian cultural holiday, 8th February 2011, in the atrium of the national Museum at Prešernova in Ljubljana at a cultural event entitled the third dimension of the Vače situla. The visitors had the opportunity to test the new technology of remote control of 3D objects as well as 3D scanning and capturing the shape and texture of material objects. The public response was very favourable indicating the importance of modern technological approaches in presenting our cultural heritage. The value of 3D technologies in capturing and visualisation of cultural heritage was proved: 1. they enable multiuser and interactive access to 3D content, 2. 3D metadata serve for educational purposes, public presentations, exhibitions, and promotion of cultural heritage, 3. they offer new opportunities to spread information on cultural heritage objects, 4. virtual objects are presented in a user friendly, intuitive and attractive way.
Keywords: archaeology; arheologija; arheološke najdbe; cultural heritage; kulturna dediščina; situla; Vače; muzejske zbirke; digitalizacija; digitization; vizualizacija; 3D; Narodni muzej Slovenije; National Museum of Slovenia